The Impact of Knowledge Sharing and Organizational Learning Capacity on Innovation Performance (Case Study of Wonosobo District Regional Library Staff) - Bawazir, Hilda Retno Asih; Saputri, Ayu; Saputra, Yoga Dwiki; Affandi, Achmad (UM Purwokerto Press, 2025)
The purpose of this studies is to take a look at how know-how sharing and organizational mastering abilties effect innovation overall performance. The cognizance of this studies is whether or not know-how sharing impacts the overall performance of Wonosobo Regency Arpusda employees, whether or not organizational mastering capabilities have an impact on the overall performance of Wonosobo Regency Arpusda employees, and whether or not know-how sharing and organizational mastering capabilities have an impact on the overall performance of Wonosobo Regency Arpusda employees. Data changed into amassed the use of a quantitative approach thru a questionnaire that changed into introduced to 38 Arpusda workforce members. Multiple linear regression evaluation changed into used to check the studies hypothesis. The outcomes of the studies display that know-how sharing has a high quality and sizeable impact at the innovation overall performance of Wonosobo Regency Arpusda employees. Organizational mastering abilties even have a high quality and sizeable impact at the innovation overall performance of Wonosobo Regency Arpusda employees.